1995
DOI: 10.1002/mc.2940140105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genetic background on tumorigenesis in p53‐deficient mice

Abstract: Mice with disrupted germline p53 alleles have been engineered by us and others and have been shown to have enhanced susceptibility to spontaneous tumors of various types. We monitored a large number of p53-deficient mice (p53+/- and p53-/-) and their wild-type littermates (p53+/+) of two different genetic backgrounds (129/Sv and mixed C57BL/6 x 129/Sv) up to 2 yr of age. p53+/- and p53-/- 129/Sv mice show accelerated tumorigenesis rates compared with their p53-deficient counterparts of mixed C57BL/6 x 129/Sv g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
173
4
4

Year Published

1998
1998
2006
2006

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(206 citation statements)
references
References 18 publications
25
173
4
4
Order By: Relevance
“…The other 10 animals developed an array of tumors typical in P53 þ /À animals around 12 months of age, including rhabdomyosarcomas, osteosarcomas, and lymphomas. (Donehower et al, 1992(Donehower et al, , 1995b. The mammary tumors that did develop in the Tg DNbCat / þ , P53þ /À virgin cohort tended to be similar to the Tg DN-bCat / þ , P53 þ / þ tumors (Figure 1a and b) and contained mainly microacinar structures with regions of disorganized tissue and some invasiveness (data not shown).…”
Section: Pathology Of Mammary Tumorsmentioning
confidence: 82%
See 2 more Smart Citations
“…The other 10 animals developed an array of tumors typical in P53 þ /À animals around 12 months of age, including rhabdomyosarcomas, osteosarcomas, and lymphomas. (Donehower et al, 1992(Donehower et al, , 1995b. The mammary tumors that did develop in the Tg DNbCat / þ , P53þ /À virgin cohort tended to be similar to the Tg DN-bCat / þ , P53 þ / þ tumors (Figure 1a and b) and contained mainly microacinar structures with regions of disorganized tissue and some invasiveness (data not shown).…”
Section: Pathology Of Mammary Tumorsmentioning
confidence: 82%
“…Loss of P53 is associated with dramatic genomic instability and as a result increased mutational events in tumors (Donehower et al, 1995b;Venkatachalam et al, 1998). Given the long latency of tumor initiation in our stochastic MMTV-DNb-catenin mice, we expect that secondary mutation is essential for tumorigenesis in this model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A trend to tumour multiplicity has also been seen in the p53-deficient mice, but this is of modest extent. From several reports Hursting et al, 1994;Jacks et al, 1994;Kemp et al, 1994;Purdie et al, 1994;Donehower et al, 1995), tumours are almost always single in wild-type mice, multiple tumours (typically no more than two) are occasionally seen in p53+/-mice and two to four tumours are not uncommon in p53-/-mice, although lymphomas in particular may be reported as 'generalized'; for example Hursting et al (1994) recently reported a total of 67 tumours in 52 pS3-/-mice over a 48-week period, with more than one tumour observed in 35% of all tumour-bearing mice. However, tumour multiplicity always remains in single figures and the median number of distinct tumours at presentation is one for all genotypes.…”
mentioning
confidence: 99%
“…This allows the number of stages to become a controlled variable in tumorigenesis experiments, a possibility which did not exist until recently. Donehower et al (1995 Experimental data are now available on the time of tumours developing spontaneously in wild-type and p53-deficient mice. The tumours are of several types, but the majority (in all genotypes) are lymphomas, with sarcomas the next most frequent category.…”
mentioning
confidence: 99%